All‐Solid‐State Garnet‐Based Lithium Batteries at Work–In Operando TEM Investigations of Delithiation/Lithiation Process and Capacity Degradation Mechanism. Issue 5 (18th December 2022) - Hou, An‐Yuan; Huang, Chih‐Yang; Tsai, Chih‐Long; Huang, Chun‐Wei; Schierholz, Roland; Lo, Hung‐Yang; Tempel, Hermann; Kungl, Hans; Eichel, Rüdiger‐A.; Chang, Jeng‐Kuei; Wu, Wen‐Wei
Abstract: Li7 La3 Zr2 O12 (LLZO)‐based all‐solid‐state Li batteries (SSLBs) are very attractive next‐generation energy storage devices owing to their potential for achieving enhanced safety and improved energy density. However, the rigid nature of the ceramics challenges the SSLB fabrication and the afterward interfacial stability during electrochemical cycling. Here, a promising LLZO‐based SSLB with a high areal capacity and stable cycle performance over 100 cycles is demonstrated. In operando transmission electron microscopy (TEM) is used for successfully demonstrating and investigating the delithiation/lithiation process and understanding the capacity degradation mechanism of the SSLB on an atomic scale. Other than the interfacial delamination between LLZO and LiCoO2 (LCO) owing to the stress evolvement during electrochemical cycling, oxygen deficiency of LCO not only causes microcrack formation in LCO but also partially decomposes LCO into metallic Co and is suggested to contribute to the capacity degradation based on the atomic‐scale insights. When discharging the SSLB to a voltage of ≈1.2 versus Li/Li +, severe capacity fading from the irreversible decomposition of LCO into metallic Co and Li2 O is observed under in operando TEM. These observations reveal the capacity degradation mechanisms of the LLZO‐based SSLB, which provides important information for future LLZO‐based SSLB developments. Abstract : Li7 La3 Zr2 O12 ‐based all‐solid‐state Li battery is made to deliver a high areal capacity and stable cycle performance. In operando transmission electron microscopy is performed to observe the charge/discharge processes while three capacity degradation mechanisms, that is, interface delamination, microcrack formation, and LiCoO2 decomposition, are revealed.